The Linguistic Dimension of Restaurant Menus: Reflections on Language Education, Culture, and Social Mentalities - Troplini (Abdurahmani), Edlira; Shosha, Bitila; Metushaj, Mirela; Lluri, Luiza (European Journal of Social Science Education and Research, 2025)
This study builds upon previous research conducted recently and highlights the influential role of language as a crucial catalyst for ensuring success across various aspects of daily life. Moreover, the mission of language is closely linked to fostering individual awareness through the process of linguistic education, emphasizing its role, significance, and weight in every sphere of human existence. The topic of this study is directly related to the social dynamics that shape language use, linguistic evolution across diverse contexts, and the intrinsic value of language choice, as well as phenomena such as linguistic individualism, conformism, bilingualism, multilingualism, and language variation across time and space. All these elements are clearly interwoven within the field of culinary arts, a domain that bridges specificity and interdisciplinarity. More specifically, this study investigates how the written language of restaurant menus embodies and communicates culinary creativity.These phenomena must be considered in the formulation of language education policies, with the aim of integrating them into language teaching across all educational cycles. They are distinctly intertwined with multiple fields, both specific and general, innovative and contemporary, linguistic and interdisciplinary. The language use in restaurant menus (as a basic argument of this study) constitutes the most interesting instrument that conveys culinary creativity. On the other hand, the restaurant menus also have the potential to reflect significant cultural intersections, tradition blending, and evolving social identities. Whether monolingual, bilingual, or multilingual, their language provides valuable insights into how cultures interact and how traditions are shared across different populations. This study further illustrates the importance of linguistic formation in shaping the contemporary citizen. Through the written language of restaurant menus, not only is revealed culinary artistry, but a wide spectrum of linguistic and socio-cultural issues is also brought into focus.